The Tagliavini Report Revisited: Jus ad Bellum and the Legality of the Russian Intervention in Georgia - Lott, Alexander (Utrecht Journal of International and European Law, 2012)
The purpose of this manuscript is to critically examine the legal findings of the Tagliavini Report in hope of contributing to the debate on its principal conclusions. The establishment of an independent fact-finding commission to explore the origins and course of the conflict marked the first time in its history that the EU, key mediator in concluding the Georgia-Russia conflict's ceasefire, intervened actively in an armed conflict. The author, disparate from the Fact-Finding Mission, does not find Georgia to have the right of self-defence in regard of attacks by Ossetian secessionist forces preceding the Russian invasion. The author argues, analogously to the Tagliavini Report, that Georgian offensive on Tskhinvali in South Ossetia represented an excessive use of force which violated Article 2(4) of the UN Charter. In regards to the central issue, the author contends that the Russian military intervention in Georgia on 8 August 2008 following Georgian offensive on Tskhinvali was not justified under the scope of reinforcing its peacekeeping force, or on the grounds of humanitarian intervention, intervention by invitation, or protection of citizens. Distinct from the Tagliavini Report, this manuscript reaches the conclusion that Russia was neither entitled to invade Georgia for protecting its peacekeeping contingent that comprised part of an international peacekeeping force.